POSSIBILITIES OF USING ARTIFICIAL INTELLIGENCE (AI) TECHNOLOGIES IN TEACHING ENGLISH IN HIGHER EDUCATION - Kodirov Alijon Abdumannonovich; Mirhabibullayev Muhammadziyo Mirmukhsin ugli (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation: This article discusses the role, advantages, and limitations of artificial intelligence (AI) technologies in teaching English in the higher education system. AI-based tools — systems such as ChatGPT, Grammarly, Duolingo, Replika, and TalkPal - is creating new opportunities for the development of students' linguistic competence. The study analyzes practical experiences of using AI tools in higher education institutions, as well as the opinions of teachers and students.